2021
DOI: 10.1002/elps.202000245
|View full text |Cite
|
Sign up to set email alerts
|

An 18 Multi‐InDels panel for analysis of highly degraded forensic biological samples

Abstract: DNA genotyping from trace and highly degraded biological samples is one of the most significant challenges of forensic DNA identification. There is a lack of simple and effective methods for genotyping highly degraded samples. In this study, a multiple loci insertion/deletion polymorphisms (Multi-InDels) panel was designed for detecting 18 autosomal Multi-InDels through capillary electrophoresis (CE) with amplicon sizes no longer than 125 bp. Studies of sensitivity, degradation, and species specificity were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…With DNA heated for 10 h, three STR loci showed allele‐dropout with the Investigator 26plex QS Kit, while the other two kits had an entire profile with all target markers. Such results were comparable to Li's research [15].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…With DNA heated for 10 h, three STR loci showed allele‐dropout with the Investigator 26plex QS Kit, while the other two kits had an entire profile with all target markers. Such results were comparable to Li's research [15].…”
Section: Resultssupporting
confidence: 92%
“…Multi-InDel markers have such many advantages, such as high polymorphism, low mutation rate as SNP, small amplicons, and simply detected with CE instruments. Besides, many studies have concentrated on the Multi-InDel markers and several multiplex systems have been established, the probability of exclusion was approximately 0.99, which was not sufficient for parentage test [15]. It is necessary to explore new Multi-InDel markers to enrich the application in parentage test in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MM-InDel loci with three alleles accounted for 85.59% of the obtained candidates. Additionally, previous studies suggested that MM-InDels containing two InDels have three instead of four alleles ( Huang et al, 2014 ; Li et al, 2021 ), which is in line with our observation. Since it is difficult for multi-allelic InDels to repeatedly mutate into an identical allele and multi-InDels with two InDel loci presented a tri-allelic pattern in the population, a secondary mutation event could be inferred at these loci.…”
Section: Discussionsupporting
confidence: 93%
“…Li et al evaluated the effect of the temperature at the 18 multi-InDels panels by keeping DNA isolates in a water bath at 100˚C for 0, 20, 40, 60, and 80 mins. Although all loci were observed in all time intervals, peak imbalances have begun to appear in the alleles after the 40th min [24]. The denaturation of DNA begins at 95˚C…”
Section: Degradation Studiesmentioning
confidence: 97%